2014
DOI: 10.1136/annrheumdis-2014-205696
|View full text |Cite
|
Sign up to set email alerts
|

Choline kinase inhibition in rheumatoid arthritis

Abstract: Objectives Little is known about targeting the metabolome in non-cancer conditions. Choline kinase (ChoKα), an essential enzyme for phosphatidylcholine biosynthesis, is required for cell proliferation and has been implicated in cancer invasiveness. Aggressive behaviour of fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA) led us to evaluate whether this metabolic pathway could play a role in RA FLS function and joint damage. Methods Choline metabolic profile of FLS cells was determined by 1H mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 55 publications
(40 reference statements)
0
65
0
1
Order By: Relevance
“…The choline pathway is highly active in FLSs 119 . Choline kinase-α (CK), the enzyme that catalyses the first step in the cytidine-diphosphate–choline pathway, is essential for phosphatidylcholine production.…”
Section: Disease-specific Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The choline pathway is highly active in FLSs 119 . Choline kinase-α (CK), the enzyme that catalyses the first step in the cytidine-diphosphate–choline pathway, is essential for phosphatidylcholine production.…”
Section: Disease-specific Metabolic Pathwaysmentioning
confidence: 99%
“…In comparison with healthy tissue, elevated levels of CK have been associated with malignant transformation, invasion and metastasis in some human cancers 120124 . CK is expressed in synovial tissue in RA and in cultured FLSs; furthermore, a CK inhibitor suppresses the aggressive properties of cultured RA FLSs, including cell migration and resistance to apoptosis 119 . In a serum-transfer model of arthritis, pharmacological CK inhibition (compared with vehicle-only) prevented development of arthritis when administered before serum transfer, and significantly decreased levels of markers of arthritis in treatment of established disease 119 .…”
Section: Disease-specific Metabolic Pathwaysmentioning
confidence: 99%
“…The metabolomic approach enables the identification of changes in the metabolic pattern and the elucidation of variations in phenotypes imposed by perturbations such as gene modification or environmental stimuli [10,11]. Recently, metabolomics has been used to study the metabolic changes that occur in cancer cells and FLS obtained from Dupuytren's disease or RA [12][13][14][15]. Although the pathogenic behaviors of RA FLS have been studied extensively, the metabolic alterations of their transformed phenotype in RA remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As the synovium in RA shares similar characteristics with malignancies i.e. abundance of cytokines and oxygen radicals, it is tempting to speculate that choline kinase inhibition may control RA disease activity through suppression of the fibroblast-like synoviocytes (Guma et al 2015). This notion was supported by a murine study with an arthritis model which demonstrated decreased severity of arthritis with choline kinase inhibition (Guma et al 2015).…”
Section: Choline Kinasementioning
confidence: 99%